Peran Bahasa Indonesia Sebagai Pemelihara Perbatasan Wilayah Negara - Imam Santosa (Balai Bahasa Provinsi Papua, 2019)
Indonesia-PNG border poeple consist of some etnict. They lives on the good relation without friction or conflict. Language is used by them is Indonesian language, it uses on interaction between etnic. On the other word, Indonesian language in the borser of Indonesian-PNG can role as the keeper of the border zone can grow their nationality to Indonesian.